Plain Language Summary of Publication: The ProLOGUE study investigating brodalumab in people with plaque psoriasis - Shinichi Imafuku; Chika Ohata; Masaru Honma; Hidehisa Saeki; Yoko Mizutani; Takuya Miyagi; Kenta Murotani; Yasumasa Kanai (Therapeutic Advances in Chronic Disease)
What is this summary about? This summary describes the results of the ProLOGUE study, which tested the effects of brodalumab in Japanese people with plaque psoriasis using outcomes mostly reported by the study participants. What happened in the study? Seventy-three adults with plaque psoriasis received brodalumab for 48 weeks. Doctors reported the effects of brodalumab on the extent and severity of psoriasis, while study participants reported its effects on health-related quality of life, overall health status, psoriasis severity, itch, skin pain, anxiety and depressive symptoms, sleep, general activity, work productivity and income loss, and how satisfied they were with brodalumab as a treatment. What were the results? Before receiving brodalumab , study participants reported that psoriasis symptoms, particularly itching and depressive symptoms, greatly impacted them and affected their ability to take part in daily activities, work effectively, and earn an income. Brodalumab improved the extent and severity of psoriasis according to doctors, and improved health-related quality of life, overall health status, most psoriasis symptoms, general activity, work productivity, and income loss according to study participants. Brodalumab was also considered an effective, convenient, and beneficial treatment by study participants. Although brodalumab treatment was associated with improvements in the objective (doctor-assessed) measures of symptoms (Psoriasis Area and Severity Index (PASI) scores), some study participants felt their health-related quality of life was still affected by psoriasis, with itching the most troublesome remaining symptom. What do the results mean? Brodalumab effectively treats psoriasis. However, doctors and patients have different views on the effects of treatment; therefore, patients’ concerns should be taken into consideration when deciding on a treatment plan. Trial registration: You can read more about the ProLOGUE study on the following website: Japan Registry of Clinical Trials ( https://jrct.niph.go.jp/en-latest-detail/jRCTs031180037 ; jRCTs031180037). The study was conducted from October 2017 to March 2020. It is completed and there are no plans for follow-up studies.